ANALYSIS OF THE USE OF LANGUAGE IN THE FIELD OF PHONOLOGY IN THE PRESIDENT'S PRIME SPEECH AT THE UN GENERAL ASSEMBLY - Ertinawati, Yuni; Rahmadhani, Siti Zharifah Dwita; Lasaufa, Salwa; Zulfiqri, Nizar Taufik (Media Inovasi Pendidikan dan Publikasi, 2024)
This analysis aims to describe language errors in the field of phonology in the first speech of Indonesian President Joko Widodo at the 75th UN general session. This research uses a qualitative research design with a type of research that interprets research objects in various ways based on scientific studies. The data source in this research is a video on the official iNews YouTube channel entitled